El atributo de transversalidad clínica de la noción psicoanalítica adolescencia (2011)
ABSTRACT: The question about the validity of the adolescent psychoanalytical notion delimitated by psychopathology is the starting point of this article. In that way, some Freud basic premises are retaken with the target to build a first connotation from the return of the repressed, which is contrasted with clinical cases and social reality. Consequently, a second theoretical connotation is proposed from the logic of a posteriori, which is found in Freud's work, based in some relevant considerations of post-Freudians authors. Finally, consequences about its clinical scope are extracted, concluding the legitimacy of attribute through clinical structuralism of the adolescent.